MENGEKSPLORASI KOMPETENSI PENYULUH AGAMA DALAM MENYUSUN NASKAH MATERI PENYULUHAN NILAI-NILAI MODERASI BERAGAMA - Dudung Abdul Rohman; Firman Nugraha (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2022)
This research is motivated by the burden of compiling manuscripts for counseling materials to religious counselors. In fact, this is a technical competence that must be possessed by them. Moreover, competence in compiling the materials must respond to actual religious issues. Thus, there are needs in structured and measurable efforts to strengthen these technical competencies by conducting technical guidance (Bimtek) or direct assistance to the counselors at the Office of Religious Affairs (KUA). This research is qualitative-descriptive to illustrate how is religious counselors’ competence in compiling the manuscripts, focused on religious moderation values. After strengthening by the way of implementing or mentoring, then the result was obtained. There was an increase in competence although not significant, because the time was very limited. Competence in knowledge aspect has an average increase of 8 %. There is an increase of attitude, such as awareness and motivation to convey material on actual religious issues. An increase in skill aspect is in form of compiling religious moderation concepts and manuscripts with diverse values. The increase is up to the level of sufficient, though in the sense that it has not been significant yet. Then in the follow-up plan activities, from the results of interviews with related parties, information was obtained that it was important to convey actual religious materials such as religious moderation to the target groups. Even if it must be conveyed gradually so that there is no misunderstanding and first coordinate with the management of the taklim assembly.